Increased Esophageal Exposure to Weakly Acidic Reflux 5 Years After Laparoscopic Roux-en-Y Gastric Bypass. Issue 5 (November 2016) - Rebecchi, Fabrizio; Allaix, Marco E.; Ugliono, Elettra; Giaccone, Claudio; Toppino, Mauro; Morino, Mario
Abstract : Objective: To evaluate the long-term effects of laparoscopic Roux-en-Y Gastric Bypass (LRYGB) on gastroesophageal function. Background: LRYGB is considered the weight loss procedure of choice for obese patients with gastroesophageal reflux disease (GERD). However, long-term instrumental evaluations of GERD after LRYGB are not available. Methods: Morbidly obese patients selected for LRYGB were included in a prospective study. We performed clinical evaluation with GERD-HRQoL questionnaire, upper endoscopy, esophageal manometry, and 24-hour impedance pH (24-hour MII-pH) monitoring preoperatively and at 12 and 60 months after surgery. This trial is registered with ClinicalTrials.gov (no. NCT02618044). Results: From May 2006 to May 2009, 86 patients entered the study and 72 (84%) completed the 5-year protocol. At preoperative 24-hour MII-pH monitoring, 54 patients (group A) had normal values, whereas 32 (group B) had diagnosis of GERD: 23 had acidic reflux, whereas 9 had combined reflux [acidic + weakly acidic reflux (WAR)]. The groups were similar in preoperative age, body mass index, and comorbidities. At 12 and 60 months, significant improvement in questionnaire scores was observed in group B patients. No manometric changes occurred in both groups; 24-hour MII-pH monitoring showed a significant reduction in acid exposure, but an increase of WAR in both group A (from 0% to 52% to 74%) and group B (from 35% to 42% to 77%). At long-term follow-up, esophagitis was found in 14 group A (30%) and in 18 group B patients (69%) ( P < 0.001). Conclusions: LRYGB allows to obtain an effective GERD symptom amelioration and a reduction in acid exposure. However, 3 out 4 patients present with distal esophagus exposure to WAR.